Otosclerosis: audiometric results and quality of life after stapedectomy with interposition or CO2 laser-calibrated stapedotomy without interposition. (1st March 2023) - Maalouf, Ramzi R.; Marc, Morgane; Mukherjee, Payal; Van Rompaey, Vincent; Eliezer, Michael; Hautefort, Charlotte; Verillaud, Benjamin; Herman, Philippe; Kania, Romain
Abstract: Background: The surgical treatment of otosclerosis consists of the replacement of the stapes using a piston. Aims/Objectives: The objective of this study is to assess the audiometric results and quality of life (QOL) of patients who underwent surgery for otosclerosis by stapedectomy with fascia interposition (STIP) or by stapedotomy using CO2 laser (SLaser) without fascia interposition. Material and Methods: Ninety-one patients operated on for otosclerosis by STIP (40 patients) and by SLaser (51 patients) were included. Audiometric results were graphically displayed using the Amsterdam Hearing Evaluation Plot and were compared to the Common Otology Database (COD) comprising 660 patients. The patients' QOL was assessed with an otological validated survey. The significance level was p < .05. Results: There was no significant difference in hearing improvement between SLaser and STIP-operated patients. There was no significant difference between our results and that of COD. QOL was significantly improved (+3.5/10) postoperatively for both STIP and SLaser in both social and professional fields. Conclusions and Significance: By comparing QOL and hearing gain of STIP and SLaser, our results suggest that both surgical techniques are a safe and successful treatment for otosclerotic stapes fixation. Further studies aiming at comparing larger series may confirm and refine these results.